Trend Analysis of Positive Sentiment for Special Autonomy for Papua on Twitter - Lawelai, Herman; Sadat, Anwar (Jurnal Bina Praja, 2022)
Technological Advances encourage internet users on mobile phones or other communication tools to access or obtain information via social media, including conversations on social media on Twitter, about the implementation of Provincial special autonomy. This research method utilizes Twitter data crawled by the Drone Emprit Academic application with the keyword " special autonomy of Papua." The study analyzed 170,641 mentions collected on Twitter with the tweet "Special Autonomy for Papua." The results of this study show that the community's response to Papua's special autonomy from February 1, 2021, to February 1, 2022, was 170,641 mentions. The results of this study showed the public reaction to conversations related to Papuan special autonomy on Twitter that positive sentiment dominated with 124,181 (73 percent) mentions, followed by negative sentiment with 37,570 (22 percent) mentions, and neutral sentiment with 8,890 (5 percent) mentions. The results of this study contribute to understanding the dominant topic of Papua's special autonomy, which can be used as a reference by the government in supporting policies and improving service quality through Papua's special autonomy.